Lessons [large type] - McEwan, Ian (Random House Large Print, 2022)
When the world is still counting the cost of the Second World War and the Iron Curtain has descended, young Roland Baines's life is turned upside down. He is two thousand miles from his mother's protective love, stranded at an unusual boarding school, when his vulnerability attracts his piano teacher, Miriam Cornell, leaving scars as well as a memory of love that will never fade.